2017
DOI: 10.1016/j.margeo.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, age and sediment dynamics of the upper headwall of the Sahara Slide Complex, Northwest Africa: Evidence for a large Late Holocene failure

Abstract: The Sahara Slide Complex in Northwest Africa is a giant submarine landslide with an estimated runout length of ~ 900 km. We present newly acquired high-resolution multibeam bathymetry, sidescan sonar, and sub-bottom profiler data to investigate the seafloor morphology, sediment dynamics and the timing of formation of the upper headwall area of the Sahara Slide Complex. The data reveal a ~35 kmwide upper headwall opening towards the northwest with multiple slide scarps, glide planes, plateaus, lobes, slide bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 67 publications
1
36
0
1
Order By: Relevance
“…From the limited cases reported in the literature, the Storegga Slide shows turbidite rates ranging from 7.8% to 10.4% (Haflidason et al, ), values that are similar to the turbidite rates calculated in this work. However, some major landslides do not show any associated turbidites (e.g., the Sahara Slide on the northwest African continental margin; Georgiopoulou et al, ; Li et al, ). In some steeper continental slopes, turbidite rates may be much larger than those reported in this work as turbidity currents often incorporate significant volumes of seafloor sediment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the limited cases reported in the literature, the Storegga Slide shows turbidite rates ranging from 7.8% to 10.4% (Haflidason et al, ), values that are similar to the turbidite rates calculated in this work. However, some major landslides do not show any associated turbidites (e.g., the Sahara Slide on the northwest African continental margin; Georgiopoulou et al, ; Li et al, ). In some steeper continental slopes, turbidite rates may be much larger than those reported in this work as turbidity currents often incorporate significant volumes of seafloor sediment.…”
Section: Discussionmentioning
confidence: 99%
“…The three latter processes are considered in the literature as generating the main components of mass‐transport deposits (MTDs) and can be identified on seismic data (e.g., Bull et al, ; Moscardelli & Wood, ). In addition, turbidites generated during slope failure are commonly observed on sediment cores as they cover very large areas of continental slopes and ocean basins (e.g., Li et al, ; Masson et al, ; Owen et al, ; Piper et al, ). Detailed estimates of the volume of MTDs (Vm; see Text S1 for the detailed terminology definition; Figure a) on seismic data, and morphological analyses of seafloor scars using multibeam bathymetric data, are key to calculate the residual volume of failed strata after their emplacement (Vr; Figure ) (e.g., Alves & Cartwright, ; Calvès et al, ; Lamarche et al, ; ten Brink et al, ; Vӧlker, ).…”
Section: Introductionmentioning
confidence: 99%
“…These two surfaces may represent two unrelated events or represent different slip planes within a single landslide complex. Infill of Surface 1 prior to erosion by Surface 2 indicates several depositional episodes rather than different phases of the same event, similar to the Hinlopen Slide (Vanneste et al ., ) or the Sahara Slide Complex (Li et al ., ). If Surfaces 1 and 2 represent the basal shear surfaces that coalesce up‐dip into the headwall of a larger slide, this could be the characteristic of retrogressive erosional events (Piper et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Failures can form a single submarine landslide or a composite landslide complex (e.g. Gee et al ., ; Antobreh & Krastel, ; Li et al ., ) with products of failure often treated as multiple separate events (MTDs) in seismic and outcrop data sets (e.g. Moscardelli et al ., ; Sobiesiak et al ., ; Ortiz‐Karpf et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The first scenario we may consider is that the Agadir Slide may be formed by a single-phase event but occurred along two basal shear surfaces (glide planes). Several previous studies have revealed that multiple mass wasting events can be triggered at the same time and amalgamate or erode each other (Moscardelli et al, 2006;Li et al, 2017). If this was the case for the Agadir Slide, the upper and lower headwall areas would have been generated simultaneously.…”
Section: Emplacement Processes Of the Agadir Slidementioning
confidence: 97%